Effects of antioxidant capacity-based dietary replacement of vitamin E with commercial products containing grape skin–green tea extracts or hydrolyzed wood polyphenols on poultry performance, metabolism, immune-related gene expression, and meat quality - Simoni, M.; Danese, T.; Mezzasalma, N.; Goi, A.; Pitino, R.; Mantovani, G.; Andrani, M.; Costa, A.; Plomaritou, A.; Ragionieri, L.; Tsiplakou, E.; De Marchi, M.; et al. (Frontiers in Veterinary Science, 2025)
Natural antioxidants are widely investigated as potential substitutes for synthetic compounds suitable for use in organic diets. They are often included in diets based on literature and manufacturer recommendations, sometimes leading to inconsistent results. In this study, we replaced 0.05 g/kg of vitamin E in poultry diets (vitE) with commercial products containing grape skin and green tea extracts (GSGT) or hydrolyzed wood polyphenols (HWP), at doses calculated based on their in vitro antioxidant capacity measured by the 2.2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) test (ABTS). A total of 252 one-day-old male Ross 308 chicks, reared according to organic farming guidelines, were assigned to 9 pens in a randomized block design with 3 replicates per dietary treatment; 108 were slaughtered at 42 days as in the conventional production cycle, while the remaining were slaughtered at 84 days, in accordance with organic farming regulations. Overall, no differences were observed in performance, antioxidant capacity, hematological parameters, carcass and cut weights, meat quality, and survival rate among the dietary treatments. The control group had the highest plasma vitamin E levels (p < 0.0001), while at 42 days, the HWP diet increased plasma vitamin A (p = 0.041) and reduced ALT-GPT levels (p = 0.008). The GSGT diet reduced creatinine levels (p < 0.0001) and showed higher meat protein content compared to HWP (p = 0.024). Differences in gut histomorphology were observed at 42 and 84 days, with effects on specific intestinal regions. Natural antioxidants modulated immune-related gene expression, maintaining the innate immune system in an “alert” state compared to control. The GSGT and vitE groups showed the highest European Production Efficiency Factor (EPEF) at 42 days, while at 84 days, a higher EPEF was observed for the HWP and GSGT groups. In conclusion, HWP and GSGT can effectively replace vitamin E in poultry diets when balanced for antioxidant capacity, in both conventional and organic diets.